Migration, dispossession, post-memorial recuperations: an ‘undisciplined’ view of the partition of the Indian subcontinent - Juneja, Monica (Handbook of art and global migration, 2019)
Das Kapitel Migration, Dispossession, Post-Memorial Recuperations erschien in Handbook of Art and Global Migration auf Seite 298.